2024
DOI: 10.1186/s40991-024-00091-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of corporate social responsibility communication on nonprofit organisations in South Africa

Sabryna Joanne Tsinga-Mambadja,
Hilda Bongazana Dondolo,
David Pieter Conradie

Abstract: The aim of the study was to investigate whether the content of Corporate Social Responsibility (CSR) messages predicts communication outcomes in South African nonprofit organisations (NPOs). The study found a positive association between CSR message content and CSR communication outcomes. Additionally, CSR message content in nonprofit organisations is positively linked to their CSR communication outcomes. Furthermore, support for community-related activities positively impacts CSR communication outcomes, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Ethical leadership significantly impacts CSR, especially in industries like construction, where ethical considerations are crucial due to their environmental and social effects (Ayoko, 2022). A study by Tsinga-Mambadja et al (2024) revealed how significantly communicating CSR affects nonprofit organizations in South Africa. The research found that leadership styles, like transformational and ethical leadership, are closely connected to CSR practices, with participative leadership also playing a role.…”
Section: Discussionmentioning
confidence: 99%
“…Ethical leadership significantly impacts CSR, especially in industries like construction, where ethical considerations are crucial due to their environmental and social effects (Ayoko, 2022). A study by Tsinga-Mambadja et al (2024) revealed how significantly communicating CSR affects nonprofit organizations in South Africa. The research found that leadership styles, like transformational and ethical leadership, are closely connected to CSR practices, with participative leadership also playing a role.…”
Section: Discussionmentioning
confidence: 99%